Chapter Colonization of transplanted Posidonia Oceanica: understanding the spatial dynamics through high-spatial resolution underwater photomosaics - Ardizzone, Giandomenico (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Following the restoration of a P. oceanica meadow impacted by the Concordia shipwreck, we investigated the spatial dynamic of the most important and protected Mediterranean endemic seagrass over a two-year period applying three spatial metrics: number of patches, mean patch size and total cover. By means of underwater photomosaics, we noticed a diminution in the number of patches in favour of the mean size and total cover. The outcomes showed that, under suitable environmental conditions, P. oceanica colonizes rapidly the dead matte substrate.